2002
DOI: 10.1109/jmems.2002.802905
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal silicon nano-wire piezoresistors for mechanical sensors

Abstract: A p-type silicon (Si) nano-wire piezoresistor, whose minimum cross-sectional area is 53 nm 53 nm, was fabricated by combination of thermal diffusion, EB (electron beam) direct writing and RIE (reactive ion etching). The maximum value of longitudinal piezoresistance coefficient [011] of the Si nano-wire piezoresistor was found to be 48 10 5 (1/MPa) at surface impurity concentration of 5 10 19 (cm 3) and it has enough sensitivity for mechanical sensor applications. The longitudinal piezoresistance coefficient [0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 19 publications
4
60
1
Order By: Relevance
“…The use of nanocrsytalline silicon as an active material improves the performance of pressure sensors without considerably increasing the cost and complexity of fabrication. It has been observed that nanocrystalline porous silicon has the potential for improving the performance of the pressure sensors due to its increased piezoresistive coefficient of about 54.8% (Toriyama et al, 2002). Tailoring the dimensions of the nanocrystallites, which depends on the formation parameters, may modify the performance of the nanocrystalline porous silicon pressure sensor.…”
Section: Porous Silicon Pressure Sensormentioning
confidence: 99%
“…The use of nanocrsytalline silicon as an active material improves the performance of pressure sensors without considerably increasing the cost and complexity of fabrication. It has been observed that nanocrystalline porous silicon has the potential for improving the performance of the pressure sensors due to its increased piezoresistive coefficient of about 54.8% (Toriyama et al, 2002). Tailoring the dimensions of the nanocrystallites, which depends on the formation parameters, may modify the performance of the nanocrystalline porous silicon pressure sensor.…”
Section: Porous Silicon Pressure Sensormentioning
confidence: 99%
“…Silicon nanowire (SiNW) is also a candidate as a nanoscale component for mechanical or chemical sensing [13][14][15][16][17][18][19]. The piezoresistive strain gauge performs better when the dimensions are reduced [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The piezoresistive strain gauge performs better when the dimensions are reduced [16,17]. The higher surface-to-volume ratio provides a higher sensitivity to chemical…”
Section: Introductionmentioning
confidence: 99%
“…Recently, developments in the fabrication process have resulted into submicron piezoresistive cantilevers with pN [6] and even fN [7] resolution. However, most of these force sensors are limited in their application because they employ vertical structures [3,4,6,8].…”
Section: Introductionmentioning
confidence: 99%